Pine cone mold: a toolbox for fabricating unique metal/carbon nanohybrid electrocatalysts. Issue 48 (29th November 2019) - Han, Hyunwoo; Noh, Seonmyeong; Chae, Sunbin; Kim, Semin; Choi, Yunseok; Le, Thanh-Hai; Chang, Mincheol; Kim, Hyungwoo; Yoon, Hyeonseok
Abstract : Nature presents delicate and complex materials systems beyond those fathomable by humans. This work demonstrates the use of pine cones as a biomass mold for creating new metal/carbon nanohybrids. Abstract : Nature presents delicate and complex materials systems beyond those fathomable by humans, and therefore, extensive effort has been made to utilize or mimic bio-materials and bio-systems in various fields. Biomass, an inexhaustible natural materials source, can also present good opportunities for the development of unprecedented, advanced materials and processing systems. Herein, we demonstrate the use of pine cones as a biomass mold for creating new and useful metal/carbon nanohybrids (MCNHs). The inherent water-induced folding actuation of the cone scales allows the casting of an aqueous solution of a single metal precursor or a binary metal mixture into the cone mold by simply immersing the cone in the solution. The cone actively absorbs aqueous-phase metal precursors through the bract scales and the precursor ions introduced into the cone are anchored to the functional groups of the interior tissues of the cone. Subsequent heat treatment successfully led to the formation of unique MCNHs. Iron, manganese, and cobalt were employed as model metals, binary mixtures of which were also cast into the cone mold to create further versatile MCNHs. Nanoparticulate metals were formed on the carbon supports, where the size, size distribution, and crystallinity of the nanoparticles were highly dependent on the identity of the single-component precursor and the combination of precursors. Consequently, the electrochemical activity of the MCNHs also depended on which metal precursors were cast into the cone mold. The MCNH prepared from the mixture of iron and manganese precursors (MFeMn CNH) showed the best electrochemical activity. As model applications, MFeMn CNH was applied to electrode materials for electrochemical charge storage and the oxygen evolution reaction. An electrochemical capacitor cell based on the MFeMn CNH electrodes showed excellent performance with energy densities of 38.7–54.2 W h kg −1 at power densities of 16 000–160 kW kg −1 . In addition, MFeMn CNH demonstrated a low overpotential of 464 mV and fast kinetics with a Tafel slope of 64.6 mV dec −1 as an electrocatalyst for the oxygen evolution reaction in 1.0 M KOH. These results substantiate that pine cones as a biomass mold show great promise for creating versatile MCNHs through further combination of various precursors.